Being ahead of the game—the association between executive functions and football performance in high-level football players - Radke, L.; Mertens, A.; Spielmann, J.; Mayer, J. (German Journal of Exercise and Sport Research, 2023)
The current study examined the association between executive functions and the performance of high-level football players. Participants of the study (N= 176) were male football players of the same club, who played in the teams of the U12 up to the U23. Executive functions, consisting of the subcomponents cognitive flexibility, inhibition, and working memory, were assessed with the Determination Test, the Response Inhibition task, and multiple-object tracking, respectively. Football performance was operationalized through a subjective performance rating by three independent raters and an objective Footbonaut score. The Footbonaut (C-Goal GmbH, Berlin, Germany) is a football training machine which passes balls to players who then have to control the ball and pass it through highlighted squares. Using two multiple regressions—for subjective and objective performance ratings, respectively—the separate associations of the three subcomponents of the executive functions with football performance were examined. Only the score of the Determination Test (as a measure of cognitive flexibility) was significantly associated with football performance (for both the subjective and objective measures). When controlling for age, cognitive flexibility was no longer a significant predictor for athletic performance. Further research is needed to determine whether the training of cognitive flexibility in addition to physical skills might be a possible approach to further increase performance and to improve talent development in youth athletes.